عورت کی امامت:مسلم مفکرین کی آراء پر مبنی تنقیدی جائزہ: A Woman’s Leadership in Prayer: A Critical Review Based on the Opinions of Muslim Thinkers - Manzoor, Mahmooda; Ghaffar, Dr. Abdul (Al-Amīr Research Journal for Islamic Studies, 2024)
This study critically explores the contentious issue of whether a woman can lead prayers (Salat) in Islam, analyzing perspectives from classical and contemporary Muslim scholars. The article reviews the positions of the four major Sunni schools of thought—Hanafi, Maliki, Shafi’i and Hanbali—as well as Shia jurisprudence, highlighting the diversity of opinions within Islamic law. Classical scholars have generally restricted the role of women in leading prayers, especially for mixed-gender congregations, with varying allowances for women-only congregations. However, modern debates have emerged, with some scholars advocating for a reevaluation of these restrictions in light of changing social contexts and interpretations of Islamic texts. This study also examines the influence of cultural and historical factors on the evolving views regarding women’s leadership in prayer. By critically assessing these diverse perspectives, the article aims to contribute to the ongoing discourse on gender roles within Islamic practice, offering insights into the complexities and nuances of religious leadership and authority in Islam. Keywords: leading the prayer, women, Sunni schools of thought, Muslim thinkers, historical factors.